2017
DOI: 10.1177/1352458517733551
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for pediatric-onset multiple sclerosis

Abstract: Pediatric and adult MS share many genetic variants suggesting similar biological processes are present. MHC variants beyond HLA-DRB1*15:01 and HLA-A*02 are also associated with POMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 33 publications
(62 reference statements)
2
55
0
1
Order By: Relevance
“…Twenty‐eight non‐MHC variants studied were also significantly associated. Similar results were reported by the first genome‐wide association study in paediatric multiple sclerosis . Further studies will be required to evaluate the relevance of these single‐nucleotide polymorphisms but it is likely they will lead to an enhancement of our understanding of the pathophysiology underlying multiple sclerosis.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaysupporting
confidence: 77%
See 3 more Smart Citations
“…Twenty‐eight non‐MHC variants studied were also significantly associated. Similar results were reported by the first genome‐wide association study in paediatric multiple sclerosis . Further studies will be required to evaluate the relevance of these single‐nucleotide polymorphisms but it is likely they will lead to an enhancement of our understanding of the pathophysiology underlying multiple sclerosis.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaysupporting
confidence: 77%
“…Genetic susceptibility has long been established in adult‐onset multiple sclerosis, the presence of HLA‐DRB1*15:01 being the strongest genetic predictor. One of the largest case–control studies (569 cases) to date identified a shared association in paediatric multiple sclerosis with HLA‐DRB1*15:01 , with an odds ratio of 2.95, suggesting similar biological processes regardless of age at onset . Twenty‐eight non‐MHC variants studied were also significantly associated.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaymentioning
confidence: 96%
See 2 more Smart Citations
“…Participants were asked to give blood samples, which were genotyped on an Illumina custom array, the MS replication chip 14. Genotypes in the major histocompatibility complex region from the custom array were used to impute human leucocyte antigen ( HLA)-DRB1 and HLA-A alleles with HLA*IMP02 ,15 described in detail elsewhere 16. Single nucleotide polymorphisms with <2% minor allele frequency, genotyped in <98% of individuals or not in Hardy Weinberg equilibrium among controls (p<0.0001) were excluded.…”
Section: Methodsmentioning
confidence: 99%